Deteksi Dini Risiko Diabetes Melitus melalui Pemeriksaan Gula Darah pada Remaja Putri - Dwi Lestari, Yusri; Ahmad Kholid Fauzi (Health Care : Journal of Community Service, 2025)
The rising prevalence of Type 2 Diabetes Mellitus among young populations is becoming an alarming public health issue. One of the key contributing factors is the lack of awareness and delayed early detection, particularly among adolescent girls who are vulnerable to unhealthy lifestyle changes. This community service project aimed to perform early detection of type 2 diabetes melitus risk through random blood glucose screening and interactive health education for seventh-grade female students at SMP Nurul Jadid. The method involved random blood glucose testing using calibrated digital glucometers on 42 participants, followed by health education sessions through lectures and discussions, and evaluation using pretest and posttest questionnaires. Results showed that 21.4% of participants were in the prediabetes category, while the average knowledge score increased significantly from 56.2 to 92.6 after the education session. Participants also demonstrated high levels of active engagement and interest in health-related topics. These findings highlight the importance of early detection and school-based health education in preventing type 2 diabetes melitus. This activity proved effective in improving students' knowledge and awareness and holds strong potential to be developed into a sustainable preventive health program within the educational environment.